(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Poisoning from Organophosphates (OPs), especially Dichlorvos (DDVP) has become endemic due to the increasing use in house hold and agricultural pests control, with most marked effects in the nervous system. However, it is evidenced that natural antioxidants are efficacious against OPs toxicity. Thus, this study investigated the possible antidotal efficacy of Nigella sativa oil (NSO) in Dichlovos (DDVP) induced oxidative and neuronal damages in Wistar rats. DDVP was administered at sub-chronic daily dosage of 8.8 mg/kg.bw for 7 days and a post-administration of NSO at 1 ml/kg.bw for the subsequent 7 days. The rats were euthanized on the 15thday, blood sample collected via cardiac puncture, centrifuged and the plasma used for biochemical analysis of total antioxidant capacity (TAC), reduced glutathione (GSH) and total reactive oxygen species (ROS), while the frontal, occipital and cerebellar cortices and the medulla were removed for histo-morphological examinations. The results showed significant (P≤0.05) decrease in plasma TAC and GSH, while a significant (P≤0.05) increase in ROS was recorded, and some vacuolation around the neurons especially in the frontal and cerebellar cortices following DDVP exposure. However, post treatment with NSO was observed to be efficacious in the recovery of the oxidative activities and the neuro-architectural integrities. Thus, it can be concluded that the antioxidant capacity of NSO could be efficacious against OPs induced oxidative damages, especially in dichlorvos accidents.